If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -9x = 87 + -3x Solving 9 + -9x = 87 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 9 + -9x + 3x = 87 + -3x + 3x Combine like terms: -9x + 3x = -6x 9 + -6x = 87 + -3x + 3x Combine like terms: -3x + 3x = 0 9 + -6x = 87 + 0 9 + -6x = 87 Add '-9' to each side of the equation. 9 + -9 + -6x = 87 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = 87 + -9 -6x = 87 + -9 Combine like terms: 87 + -9 = 78 -6x = 78 Divide each side by '-6'. x = -13 Simplifying x = -13
| 5(2x+3)=4(3x+2)-3 | | 5x-2=4(x+1) | | 4(x-6)=6(x+2) | | 5(x+5)+9= | | 23x+-8+-14x=10 | | 2x+14=5x-8 | | n-4n-22=7n | | x(3+5)=7x-3 | | 2(x-4)+2x=32 | | 112-2x=5x-7 | | 2x-3-8x=-27 | | 1-3x(x-1)= | | 8x-7=9x+12 | | -147=-3+8a | | 4-6x=12x-7 | | 14(x^2)(y^2)+9xy-18=0 | | a/7+4=2 | | 5p-30=12 | | -1=5-4x-10-x+45 | | 4b+16=35 | | 3=-3k+9 | | 2(m+3)+1=23 | | 5x-10x+14=-3x+6 | | 3+y/4=1.95 | | 2t+38=5(t+1) | | x+4+6x-6=180 | | 23x-8-14x=21 | | x+5+x=10 | | -2(x-4)=-16 | | x+4=6x-6 | | 0=3x-9-4x | | 5x+-3=-18 |